Dynamic Holocene glacial history of St. Jonsfjorden, Svalbard. (July 2017) - Farnsworth, Wesley R.; Ingólfsson, Ólafur; Noormets, Riko; Allaart, Lis; Alexanderson, Helena; Henriksen, Mona; Schomacker, Anders
Abstract : Evidence of a dynamic Holocene glacial history is preserved in the terrestrial and marine archives of St. Jonsfjorden, a small fjord‐system on the west coast of Spitsbergen, Svalbard. High‐resolution, remotely sensed imagery from marine and terrestrial environments was used to construct geomorphological maps that highlight an intricate glacial history of the entire fjord‐system. The geomorphology and stratigraphy indicate an early Holocene local glacier advance constrained to the Lateglacial–early Holocene transition. Identification and 14 C dating of the thermophilous bivalve mollusc Modiolus modiolus to 10.0±0.12 cal. ka BP suggest a rapid northward migration of the species shortly after deglaciation. Further evidence enhances the understanding of the onset and subsequent climax of the Neoglacial‐Little Ice Age in inner St. Jonsfjorden. The present‐day terminus of Osbornebreen, the dominating glacier system in St. Jonsfjorden, is located over 8.5 km up‐fjord from its Neoglacial maximum extent. Cross‐cutting relationships suggest subsequent advances of all the smaller glaciers in the area following the break‐up of Osbornebreen. Glacial deposits, landforms and their cross‐cutting relationships observed in both terrestrial and marine settings imply a complex and highly dynamic environment through the later part of the Holocene.